All About Pandemics (Epidemic of Infectious Disease) - Lacroix, Victoria, author 648226 (Delhi, India : The English Press, 2012)
A pandemic (from Greek növ pan "all" + 8uoç demos "people") is an epidemic of infectious disease that is spreading through human populations across a large region; for instance a continent, or even worldwide. A widespread endemic disease that is stable in terms of how many people are getting sick from it is not a pandemic. Further, flu pandemics exclude seasonal flu, unless the flu of the season is a pandemic. Throughout history there have been a number of pandemics, such as smallpox and tuberculosis. More recent pandemics include the HIV pandemic and the 2009 flu pandemic. The World Health Organization (WHO) has produced a six-stage classification that describes the process by which a novel influenza virus moves from the first few infections in humans through to a pandemic. This starts with the virus mostly infecting animals, with a few cases where animals infect people, then moves through the stage where the virus begins to spread directly between people and ends with a pandemic when infections from the new virus have spread worldwide. A disease or condition is not a pandemic merely because it is widespread or kills many people; it must also be infectious.